Shaping the next one hundred years : new methods for quantitative, long-term policy analysis and bibliography - Lempert, Robert J. (RAND, 2003)
The checkered history of predicting the future-e.g., "Man will never fly"--Has dissuaded policymakers from considering the long-term effects of decisions. New analytic methods, enabled by modern computers, transform our ability to reason about the future. The authors here demonstrate a quantitative approach to long-term policy analysis (LTPA). Robust methods enable decisionmakers to examine a vast range of futures and design adaptive strategies to be robust across them. Using sustainable development as an example, the authors discuss how these methods apply to LTPA and a wide range of decis.